Cultural criminology and the politics of meaning - Ferrell, Jeff (Critical criminology, 2013)
Cultural criminology focuses on situational, subcultural, and mediated constructions of meaning around issues of crime and crime control. In this sense cultural criminology is designed for critical engagement with the politics of meaning, and for critical intervention into those politics. Yet the broader enterprise of critical criminology engages with the politics of meaning as well; in confronting the power relations of justice and injustice, critical criminologists of all sorts investigate the social and cultural processes by which situations are defined, groups are categorized, and human consequences are understood. The divergence between cultural criminology and other critical criminologies, then, may be defined less by meaning than by the degree of methodological militancy with which meaning is pursued. In any case, this shared concern with the politics of meaning suggests a number of innovations and interventions that cultural criminologists and other critical criminologists might explore.